Analisis Manajemen Risiko Pada Usaha Mikro Kecil Dan Menengah NR Advertising Kota Solok - Nengsih, Novia; Abdul Rauf; Abel Oktavia; Ade Andela Puspita; Sonia (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This study aims to identify and analyze operational risks faced by NR Advertising and to formulate appropriate risk management strategies tailored to the characteristics of micro, small, and medium enterprises (MSMEs). A qualitative approach was employed using data collection techniques including in-depth interviews and direct observation. The findings identify ten types of risks, which are classified into six main categories: production and design, marketing and services, finance, procurement and logistics, general management, and technology and systems. Each risk was assessed based on its likelihood and potential impact, and subsequently mapped into a risk matrix consisting of low, medium, and high risk levels. The results indicate that three risks fall into the low-risk category, two into the medium-risk category, and five into the high-risk category requiring priority attention. This risk mapping serves as the basis for determining appropriate risk management strategies, including risk avoidance, transfer, mitigation, acceptance, exploitation, sharing, and enhancement. This study is expected to serve as a reference for MSMEs in implementing systematic and sustainable risk management practices.